Introducing municipal bond markets in Malaysia: An assessment of present market characteristics - Harun, Mukaramah; Ting, Ding Hooi; Abdullah, Hussin (Universiti Utara Malaysia, 2003)
In developed countries, urban growth has multiplied the demand for investment in basic infrastructure services such as water supply, waste removal, roads and mass transportation. At the same time, decentralization strategies have shifted the responsibility for much of these investments to the local governments. This decentralized investment requires the development of decentralized capital financing. No longer can a central government pay for local investment by raising national taxes or borrowings on international markets and using the funds simply to construct projects at the local level. The introduction of municipal bonds is one of the alternative source of funds to finance the escalating costs of financing local governments. This paper discusses the conditions underlying the development of municipal credit markets, which Malaysia can use to provide a vehicle to narrow the local government’s resource gap through debt funding.